Relationship between Cognitive Style (Impulsivity / Reflectivity) and Violence of the Tenth Grade Students in the Governorate of Ramallah and Al Bireh in Palestine - Zakia Al Rimawi; Tayseer Abdullah; Omar Al Rimawi (Sultan Qaboos University, 2015)
The study aimed to explore the relationship between cognitive style (impulsivity/reflectivity) and violence. It also aimed to know the significance of some variables, such as gender, place of residence, and type of school, in the cognitive style (impulsivity/reflectivity) and violence among students of tenth grade in the governorate of Ramallah and Al Bireh. The study sample, was randomly selected (N = 190, 86 males and 104 females). The Familiar Figure Test (Faramawi, 1986) and a specifically designed questionnaire to assess violence were used. The results indicated no relationship between impulsivity/reflectivity and violence. However, there were significant differences in cognitive method (impulsivity/reflectivity) due to gender and place of residence. While, there was no significant difference due to school type. There were differences in verbal violence, physical violence and violence toward property attributable to gender and in favour of males. Private schools were more physically violent than public schools.